A contribution to cabbage pest management by subsistence and small-scale farmers in the Eastern Cape, South Africa - Mkize, Nolwazi (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2004)
The interaction between farmers, agricultural scientists and extension workers is sometimes overlooked in agricultural entomology. In an attempt to respond to this reality this study examines some foundation of this interaction in relation to the pest management practices of subsistence and small-scale farmers and also highlights the problems that might arise in the implementation of IPM. Problems involving pests occurrence; language barriers; beliefs, knowledge and perception about insects, and visual literacy are examined. The thesis has a two-fold focus, firstly the study of pests on cabbages of subsistence farmers in Grahamstown and secondly a broader focus on other aspects such as cultural entomology, perception of insects and visual literacy specifically in relation to Xhosa speaking people in the Eastern Cape. The most important crop for emergent farmers in the Eastern Cape are cabbages, which have a variety of pests of which diamondback moths and are the most important. Traditional pest management practices tend to influence the development of IPM programmes adopted by these farmers. Eastern Cape farmers apply periodic cropping systems, which had an effect on the population densities of diamondback moth (DBM), other lepidopteran pests and their parasitoids. Considering the maximum population densities of DBM, which were 0.2 - 2.9 larvae/plant, there were no major pest problems. The availability of parasitoids, even in highly disturbed and patchy environments, showed good potential for biological control. Since some extension officers cannot speak the local farmers' language, a dictionary of insect names was formulated in their language (isiXhosa) to assist communication. Response-frequency distribution analysis showed that the dictionary is essentially complete. The literal translations of some names show that isiXhosa speakers often relate insects to people, or to their habitat or classify them according to their behaviour. Farmers from eight sites in the Eastern Cape were interviewed regarding their knowledge and perception of insect pests and their control thereof. To some extent, farmers still rely on cultural control and have beliefs about insects that reflected both reality and superstition. There is no difference between the Ciskei and Transkei regions regarding insect-related beliefs. Farmers generally lack an understanding of insect ecology. There is a need for farmers to be taught about insects to assist with the implementation of IPM. Leftover pesticides from commercial farms or detergents are sometimes used to manage the pests. When training illiterate or semi-literate farmers, it is important to understand their media literacy so as to design useful graphic and object training media. Generally farmers showed that they either understand graphic or object media depending on the features of the insects being looked at. These findings are discussed with regard to the potential development of IPM training material for subsistence and small-scale farmers in a community.
Keywords: Cabbage -- Diseases and pests; Insect pests -- Integrated control -- South Africa -- Eastern Cape; Farms, Small -- South Africa -- Eastern Cape; Agriculture -- South Africa -- Eastern Cape